Hak Aksessibilitas pada Disabilitas di Kota Pekanbaru - Nabella Puspa Rani; Rezmia Febrina (Jurnal Ilmu Hukum, 2021)
The objectives to be achieved in this research are to explain about the implementation of accessibility rights for disabilities in Pekanbaru City; and Describe the obstacles faced by the Pekanbaru City government on the implementation of accessibility rights for disabilities in Pekanbaru City. This research method is qualitative, this type of research is sociological legal research, which is to focus more on the fulfillment of accessibility rights for disabilities in Pekanbaru City based on Riau Province Regional Regulation number 18 of 2013 concerning Protection and Empowerment of Persons with Disabilities. The results and discussion in this study are that the implementation of accessibility rights for disabilities in Pekanbaru City has not been implemented properly. This can be seen from the not yet fully available physical accessibility, which is carried out on public facilities and infrastructure as well as the environment, transportation which includes accessibility to public buildings; means of worship; public road; gardening; tourist attraction; and a public cemetery in Pekanbaru City. Barriers to the implementation of accessibility rights for disabilities in Pekanbaru City are the lack of commitment from the local government and the lack of budget provided for the fulfillment of accessibility rights for disabilities in Pekanbaru City.